Kajian Teks Lontar Aji Dresti Loka Kreti - I Made Bagus Angga Putra (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
The study of Aji Dresti Loka Kreti manuscript explores the traditional Balinese literary heritage, particularly focusing on the textual structure and cultural context embedded within it. Employing a qualitative descriptive method based on literature review and interviews, this research identifies the textual components comprising the introductory (manggala), corpus, and epilogue. The findings reveal that Aji Dresti Loka Kreti contains detailed descriptions of ceremonial stages from birth to death according to Hindu customs in Bali, emphasizing human life cycles through Manusa Yadnya and Pitra Yadnya rituals. The structure highlights the integration of religious, cultural, and social values. Moreover, the text not only reflects ritualistic practices but also serves as a guideline for the Balinese society in maintaining moral conduct and spiritual balance. In conclusion, the Aji Dresti Loka Kreti is a valuable cultural asset that preserves the traditional values and provides deep insights into the socio-religious fabric of Balinese life.